LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK HOME ROOM UNTUK MENINGKATKAN SIKAP BELAJAR POSITIF SISWA KELAS X - Yusra, Johanna; Wikanengsih; Alawiyah, Tuti (IKIP Siliwangi, 2025)
This study aims to see the effectiveness, implementation and constraints of homeroom technique group guidance services to improve students' positive learning attitudes. This study uses a mixed method with a Sequential Explanatory Design research design. The subjects of this study were students of class X SMK PGRI 1 Cimahi, with a population of 108 students, and a sample of 4 students. Sampling used a random sampling technique. Data collection used a positive learning attitude questionnaire. The data analysis technique used parametric statistics, namely the t-test and the N-gain score test, which were first carried out with prerequisite tests, namely the normality test and the homogeneity test with the help of SPSS for window version 22. The results of this service indicate that group guidance services with the homeroom technique are effective in improving students' positive learning attitudes. This is evidenced by the results of the t-test obtained a sig. (2-tailed) value of 0.004 <0.05, so there is a change in the results of students' positive learning attitudes using the homeroom technique. The obstacles of the BK teacher in this study were in the students and the time and background of the BK teacher who was not originally a counselor, while the obstacles for students in this study were student confusion in following the services implemented and in students who were still shy and indifferent when discussing. Based on the results of the analysis and discussion, this study can be concluded that group guidance with the homeroom technique is effective in improving students' positive learning attitude.